Legal Theory and Raison D’etre Behind the Use Of Unfair Contract Terms - Razak, Farihana Abdul; Abd Ghadas, Zuhairah Ariff; Ghapa, Norhasliza (SCAD Independent, 2021)
This article discussed unfair contract terms, explores the relevant legal theories that underpin the use of unfair contract terms and examines the raison d’etre for using unfair terms in a contract. The qualitative and doctrinal legal research methods were used in this study. Data were obtained through documentation techniques, which included examining and analyzing several journals, books, and other related documents. Based on library research and content analysis of primary and secondary data sources, the findings indicated that the theory put forward by legal philosophers is to ensure that law and society can be balanced. The use of standard form contracts increases the implementation of unfair contract terms; nonetheless, this study found there is raison d’etre in using unfair terms, particularly in the event of safety, security, government regulatory, operational, and health concerns. Therefore, it is hoped that the study will contribute to a knowledge of contract law.